Digital Literacy Skills of Elementary School Teachers on the North Coast of East Java - Sa’idah Shibbriyah; Ermawati Zulikhatin Nuroh (AL-ISHLAH: Jurnal Pendidikan, 2023)
The purpose of this study was to assess the proficiency of teachers in the northern coastal region of East Java in the area of digital literacy. The researchers employed a qualitative research methodology, specifically utilising a phenomenological study design. Elementary school instructors are the target audience for studying digital literacy.  The findings of this study concerning the digital literacy of primary school educators are highly favourable.  The study found that there are eight indicators of digital literacy for teachers. These indicators include proficiency in operating digital media, creativity in digital spaces, collaboration in digital space, effective communication, information search and selection skills, critical thinking and content evaluation abilities, alignment of social and cultural understanding with digital spaces, and implementation of internet security measures.